Routinely evaluated clinical assays and laboratory tests [real test] and fibrosis stages of chronic hepatitis B and C - Buğdacı, Mehmet Sait; Korkmaz, Hüseyin; Demir, Ali; Bıyık, Murat; Temel, Tuncer; Göktürk, Hüseyin Savaş; Özakyol, Ayşegül; Hatemi, İbrahim and Baysal, Birol and Karaca, Çetin and et al. (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: To provide a new mathematical formula to predict liver fibrosis in patients with chronic viral hepatitis. Materials and Methods: Patients with chronic hepatitis B and C who underwent liver biopsy at different centers were included in this study. Chronic hepatitis B was defined as immunopositivity for the hepatitis B surface antigen for at least 6 months, and chronic hepatitis C was defined as positivity for HCV RNA for at least 3 months. The histological features were evaluated by the histological activity index and fibrosis. Results: In total, 1299 patients were included in the study. The distribution and the mean of the parameters of the patients were as follows: 1009 patients with chronic hepatitis B with a mean age of 45±13/years [emale/male (F/M)=47.5/52.5%] and 290 patients with hepatitis C with a mean age of 52±10.3/years [F/M=61/39%]. When the cut-off value of the REAL TEST formula“[(age x pT x AST)/(PLT/1000)]/100” in patients with hepatitis B was determined to be ≥1.37, it was found that it could predict fibrosis with 79% specificity, 78% sensitivity, 85% negative predictive value (NPV), and 70% positive predictive value (PPV) (area under the curve (AUC)=0.852, 95% CI:0.82-0.87). When the cut-off value of the REAL TEST formula in patients with hepatitis C was determined to be ≥1.99, it was found that it could predict significant fibrosis with 87% specificity, 90% sensitivity, 94.4% NPV, and 79.4% PPV (AUC:0.95, 95% CI:0.93-0.98) Conclusion: The REAL TEST formula results correlated with the pathological findings and may be a useful method for the evaluation of patients with chronic hepatitis B and C.